2019
DOI: 10.1371/journal.pone.0225395
|View full text |Cite
|
Sign up to set email alerts
|

“Anybody can make kids; it takes a real man to look after your kids”: Aboriginal men’s discourse on parenting

Abstract: BackgroundThe realms of parenting have long belonged to females. In many cultures it has been a female who has predominantly cared for and raised children. For many Aboriginal and Torres Strait Islander male parents this has resulted in them being largely overlooked from contributing to the parenting conversation. Predictably, such a dominant discourse has led to an inadequate distribution of opportunities available and a societal perception that Aboriginal and Torres Strait Islander male parents are disintere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(50 citation statements)
references
References 15 publications
(18 reference statements)
2
48
0
Order By: Relevance
“…This is important, as previous scholarship has emphasized that fatherhood represents a critical life juncture for many males, where health-related attitudes and behaviours are often reconfigured and reprioritized (Gast & Peak, 2010; Robertson, 2008; Smith et al, 2008; Umberson et al, 2010). This includes more recent literature focused on Aboriginal and Torres Strait Islander fathers (Canuto et al, 2019, 2020; Reilly & Rees, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important, as previous scholarship has emphasized that fatherhood represents a critical life juncture for many males, where health-related attitudes and behaviours are often reconfigured and reprioritized (Gast & Peak, 2010; Robertson, 2008; Smith et al, 2008; Umberson et al, 2010). This includes more recent literature focused on Aboriginal and Torres Strait Islander fathers (Canuto et al, 2019, 2020; Reilly & Rees, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This aligns strongly with scholarship about fatherhood being a critical juncture where men are more likely to adopt healthy behaviours and engage in help seeking and health service use (Gast & Peak, 2010; Robertson, 2007; Smith et al, 2008; Umberson et al, 2010). There remains room to investigate this further within the context of Aboriginal and Torres Strait Islander fathers (Canuto et al, 2019, 2020; Reilly & Ress, 2018;). Such narratives were presented, especially powerfully, throughout social media.…”
Section: Discussionmentioning
confidence: 99%
“…37,40 Yarning is also a way to help ensure Aboriginal people are engaged, informed and active participants in the research. 33,38,39 Inclusion criteria for participants included: identifying as Aboriginal, having a partner who was more than six months pregnant or a child less than 18 months old, and having spent the majority of the antenatal period in the Broome shire. We used a purposive approach to sampling and note that the successful recruitment of participants relied on the knowledge and connections of the Aboriginal researchers (ZC andES) to the Broome Aboriginal community.…”
Section: Study Design/methodologymentioning
confidence: 99%
“…shows the high value Aboriginal men place on becoming a father and how fatherhood is associated with being an attached and involved caregiver. [27][28][29][31][32][33] Findings from our study show fatherhood was considered to commence when men found out their partners were pregnant. For these men supporting their partners through the pregnancy, making positive changes to their lifestyles, and having access to information on pregnancy were identified as meaningful and demonstrative steps in their transition to fatherhood.…”
Section: Consistent With Other Contemporary Australian Research This mentioning
confidence: 99%
See 1 more Smart Citation